2017
DOI: 10.3390/ijms18112465
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Measuring Global Hydroxymethylation of White Blood Cell DNA in Prostate Cancer: Comparison to PSA in a Pilot Exploratory Study

Abstract: This is the first study investigating the clinical relevance of 5-hydroxymethylcytosine (5hmC) in genomic DNA from white blood cells (WBC) in the context of prostate cancer (PCa) and other prostate pathologies. Using an enzyme-linked immunosorbent assay, we identified significantly different distributions of patients with low and elevated 5hmC content in WBC DNA across controls and patients with prostate cancer (PCa), atypical small acinar proliferation (ASAP), and benign prostatic hyperplasia (BPH). The measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Owing to the loss of hydroxymethylation, different cancers maintain low levels of 5-hmC (Feng et al, 2015;Strand et al, 2015;Kamdar et al, 2016;Spans et al, 2016). However, Grelus et al (2017) have shown that hydroxymethylation markers cannot be single biomarkers for PCa diagnosis. They should be used as a supplement for prostate-specific antigen to diagnose PCa.…”
Section: Aberrant Dna Hydroxymethylation In Cervical and Other Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the loss of hydroxymethylation, different cancers maintain low levels of 5-hmC (Feng et al, 2015;Strand et al, 2015;Kamdar et al, 2016;Spans et al, 2016). However, Grelus et al (2017) have shown that hydroxymethylation markers cannot be single biomarkers for PCa diagnosis. They should be used as a supplement for prostate-specific antigen to diagnose PCa.…”
Section: Aberrant Dna Hydroxymethylation In Cervical and Other Cancersmentioning
confidence: 99%
“…They should be used as a supplement for prostate-specific antigen to diagnose PCa. Although hydroxymethylation can be detected in multiple cancer types, the utility of genomic hydroxymethylation in diagnosing cancer may only be restricted to one type of cancer (Grelus et al, 2017). Thus, whether DNA hydroxymethylation can be used in clinical diagnosis needs to be explored.…”
Section: Aberrant Dna Hydroxymethylation In Cervical and Other Cancersmentioning
confidence: 99%
“…The homogeneity of Caucasian patients diagnosed with BA or COPD in terms of age and sex was analyzed using a Mann–Whitney U test and a Chi-square (χ 2 ) test, respectively [ 23 ]. The χ 2 tests were next applied to determine inter-group differences in the distribution of subjects stratified based on the area of origin (urban vs. rural) and current status of smoking (non-smoker vs. smoker).…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA methylation and hydroxymethylation were determined by measuring 5-mC and 5-hmC using 5-mC DNA ELISA Kit and Quest 5-hmC TM DNA ELISA Kit (Zymo Research, Irvine, CA, USA), respectively [46, 47]. These are the most cited ELISA-based global 5-mC and 5-hmC quantification kit in the literature, and provides scientists with a quick, cost-effective and reliable alternative to chromatographic methods [48, 49]. Assays were performed according to the manufacturer’s instructions loading 100 ng of DNA per well.…”
Section: Methodsmentioning
confidence: 99%